The effects of blockchain technology on traceability and efficiency in supply chain management: a systematic literature review - Quispe Cullampe Luis Miguel (2024)
Supply chain management has become a real challenge due to ever accelerating technological innovations and organizations must not only aim to optimize supply chain processes, but also to build trust in all links of the supply network due to increased competition and supply chain expansion. Organizations need to implement an appropriate system that will improve efficiency and customer service, meet business objectives, and increase profitability. The purpose of this article is to illustrate how blockchain technology can improve traceability and supply chain efficiency by impacting business productivity. The conceptual framework of this research work is developed through a systematic literature review on the impact of the application of blockchain technology in supply chains. The Prisma methodology was used, obtaining 78 articles as references. The results show that blockchain technology has the potential to improve traceability and efficiency throughout the supply chain through cost reduction and decentralization of information. Finally, it was concluded that this leads to improved productivity of companies and a higher level of reliability with their stakeholders. This article adds to the literature on blockchain in the supply chain by focusing the research on the impact on traceability and efficiency.